Identification of pathogenic genes associated with CKD: An integrated bioinformatics approach - Ahmed, Mohd Murshad; Shafat, Zoya; Tazyeen, Safia; Ali, Rafat; Almashjary, Majed N.; Al-Raddadi, Rajaa; Harakeh, Steve; Alam, Aftab; Haque, Shafiul; Ishrat, Romana (Frontiers in Genetics, 2022)
Abstract Chronic kidney disease (CKD) is defined as persistent abnormality in structure and function of kidneys and leads to high morbidity and mortality in individuals across the world. Globally, approximately 8% to 16% of the population is affected by CKD. Proper screening, staging, diagnosis and appropriate management of CKD by primary care clinicians are essential in preventing the adverse outcomes associated with CKD worldwide. In light of this, identification of biomarkers for appropriate management of CKD is urgently required. Growing evidence have suggested the role of mRNAs and microRNAs in CKD, however, the gene expression profile of CKD is presently uncertain. The present study was aimed to identify diagnostic biomarkers and therapeutic targets for patients with CKD. The human microarray profile datasets, consisting of normal samples and treated samples were analyzed thoroughly to unveil the differentially expressed genes (DEGs). After selection, the interrelationship among DEGs was carried out to identify the overlapping DEGs, which were visualized using Cytoscape program. Further, the PPI network was constructed from String database using the selected DEGs. Then, from the PPI network, significant modules and sub-networks were extracted by applying the different centralitiesy methods (closeness, betweenness, stress, etc.) using MCODE, Cytohubba, and Centiserver. After sub network analysis we identified 6 overlapped hub genes (RPS5, RPL37A, RPLP0, CXCL8, HLA-A, ANXA1). Additionally, enrichment analysis was undertaken on hub genes to determine their significant functions. Further, these 6 genes were used to find their associated miRNAs and targeted drugs. Finally, two genes CXCL8, HLA-A were common for Ribavirin drug (gene-drug interaction), after docking studies HLA-A was selected for further investigation. To conclude our findings, we can say that the identified hub genes and its related miRNAs can serve asseveral potential diagnostic biomarkers and therapeutic targets for CKD treatment strategies.and provided a framework for further investigation.